Could threshold cycle value correctly reflect the severity of novel coronavirus disease 2019 (COVID-19)?. Issue 1 (January 2021) - Asai, Nobuhiro; Sakanashi, Daisuke; Ohashi, Wataru; Nakamura, Akiko; Yamada, Atsuko; Kawamoto, Yuzuka; Miyazaki, Narimi; Ohno, Tomoko; Koita, Isao; Suematsu, Hiroyuki; Kishino, Takaaki; Kato, Hideo; et al.
Abstract: The novel coronavirus disease 2019 (COVID-19) is diagnosed by positive result of reverse transcription polymerase chain reaction (RT-PCR) for the novel coronavirus. We concluded that cycle threshold value (Ct-value) of real-time RT-PCR (rRT-PCR) assay could decrease as patients recover. Results of rRT-PCR assay could remain positive among asymptomatic patients for longer than 2 weeks. The discharge criteria of COVID-19 patients using a negative result of rRT-PCR should be reconsidered.